Effect of anodic materials on solar photoelectro-Fenton process using a diazo dye as a model contaminant - Fajardo, Ana S. (2019)
Boron-doped diamond (BDD), Pt and Ti/RuO2 anodes were chosen to treat 118 mg L−1 Acid Blue 29 (AB29) solution in 0.050 M Na2SO4 at pH 3.0 by electrochemical oxidation with electrogenerated H2O2 (EO-H2O2), electro-Fenton (EF) and solar photoelectro-Fenton (SPEF) processes. Pseudo-first order decolourisation decays were obtained with the following order of enhancement: EO-H2O2< EF < SPEF. In EO-H2O2 are present the electrogenerated heterogeneous [rad]OH radicals on the surface of the anode, while in EF and SPEF, there is the additional influence of homogeneous [rad]OH radicals generated in the bulk by Fenton's reaction. In SPEF, the solar radiation enhances catalyst regeneration and [rad]OH generation, as well as the photolysis of Fe3+ complexes. Regarding the anodic materials, its effect was less significant in SPEF due to the predominance of homogeneous reactions. In this process, the influence of current density is more meaningful over time than as a function of charge. At the end of 15 min, applying 33.3 mA cm−2, almost complete degradation of AB29 was achieved, regardless of the anode used; 285 min after, complete mineralisation of the organic matter was reached. The energy consumption attained with BDD and Pt was quite similar, ≈ 0.11 kWh gCOD−1, whereas the Ti/RuO2 was 0.09 kWh gCOD−1. Furthermore, the evolution of short-chain carboxylic acids was followed over time and the concentration of nitrogen species was monitored. This study highlights the potential of low cost anode materials to be applied in SPEF in order to achieve a promising and competitive alternative to wastewater treatments.